Dileme sodobnega oglaševanja: Izbrane teme - Repas, Martina (2023)
Dilemmas of Modern Advertising: Selected Topics. The common theme of the monograph is various aspects of advertising goods and services. In addition to the rules on the public use of the Slovenian language in advertising, the monograph contains a comprehensive overview of the rules on advertising in the existing Slovenian legislation. In addition to the general ones, more specific topics are also included, such as comparative advertising, child protection in advertising, influencer marketing and the use of competition law rules regarding the position and responsibility of gatekeepers or digital platforms in advertising. Some new forms of advertising are discussed, such as targeted political advertising, which includes the display of customized ads about political candidates and the legal regulation of this at the EU level, as well as the protection of personal data in advertising. Other contributions relate to different areas and include advertising and scent marketing with presentation and analysis of major court cases, the position of platform workers in the advertising business and their access to collective bargaining, and issues related to advertising revenue in connection with the right to privacy.
Keywords: advertising; consumer; undertaking; competition; personal data; influencer marketing; political microtargeting platform work; legal regulation of odours; self-regulation; online platforms